The business of teaching music a guide for the independent music teacher - Siemens, Sandi (Plural Publishing, 2023)
In The Business of Teaching Music, Sandi Siemens draws upon her vast experience and a profound understanding of the business of teaching music as it pertains to the independent music teacher. Success is determined by how well prepared we are going into and operating our music teaching business. Within the covers of this book, you will discover not only all you need to know about setting up a music studio business but the secrets to operating a studio you only dreamed of having"--